Synthesis, characterization, and thermodynamic properties of poly(3-mesityl-2-hydroxypropyl methacrylate) - Acikses, Aslisah; Kaya, Ismet; Horoz, Gokhan (Wiley, 2006)
Poly(3-mesityl-2-hydroxypropyl methacrylate) (PMHPMA) was synthesized in a 1,4-dioxane solution with 2,2'-azobisisobutyronitrile as the initiator at 60 degrees C. The homopolymer and its monomer were characterized with H-1- and C-13-NMR, Fourier transform infrared, differential scanning calorimetry, thermogravimetric analysis, size exclusion chromatography, and elemental analysis techniques. According to size exclusion chromatography analysis, the number-average molecular weight, weight-average molecular weight, and polydispersity index of PMHPMA were 65,864 g/mol, 215,375 g/mol, and 3.275, respectively. According to thermogravimetric analysis, the carbonaceous residue value of PMHPMA was 14% at 500 degrees C. The values of the specific retention volume, adsorption enthalpy, sorption enthalpy, sorption free energy, sorption entropy, partial molar free energy, partial molar heat of mixing, weight fraction activity coefficient of solute probes at infinite dilution (Omega(infinity)(1)) and Flory-Huggins interaction parameter (X-12(infinity)) were calculated for the interactions of PMHPMA with selected alcohols and alkanes by the inverse gas chromatography method at various temperatures. According to Omega(infinity)(1) and X-12(infinity), selected alcohols and alkanes were nonsolvents for PMHPMA at 423-453 K. Also, the solubility parameter of PMHPMA (delta(2)) was found to be 24.24 and 26.33 (J/cm(3))(0.5) from the slope and intercept of (delta(2)(2)/RT) - x(12)(infinity)/V-1 = ((2)delta(2)/RT)delta(1) - delta(2)(2) IRT at 443 K, respectively [where 8, is the solubility parameter of the probe, V, is the molar volume of the solute, T is the column temperature (K), and R is the universal gas constant]. The glass-transition temperature of PN4HPNM was found to be 386 and 385 K by inverse gas chromatography and differential scanning calorimetry techniques, respectively. (c) 2006 Wiley Periodicals, Inc.
Keywords: chromatography; synthesis; thermodynamics; thermal properties